Immune System Evasion as Hallmark of Melanoma Progression: The Role of Dendritic Cells - Tucci, Marco; Passarelli, Anna; Mannavola, Francesco; Felici, Claudia; Stucci, Luigia Stefania; Cives, Mauro; Silvestris, Francesco (Frontiers in Oncology, 2019)
Melanoma is an immunogenic tumor whose relationship with immune cells resident in the microenvironment significantly influences cancer cell proliferation, progression, and metastasis. During melanomagenesis, both immune and melanoma cells undergo the immunoediting process that includes interconnected phases as elimination, equilibrium, and escape or immune evasion. In this context, dendritic cells (DCs) are active players that indirectly counteract the proliferation of melanoma cells. Moreover, DC maturation, migration, and cross-priming as well as their functional interplay with cytotoxic T-cells through ligands of immune checkpoint receptors result impaired. A number of signals propagated by highly proliferating melanoma cells and accessory cells as T-cells, natural killer cells (NKs), tumor-associated macrophages (TAMs), T-regulatory cells (T-regs), myeloid-derived suppressor cells (MDSCs), and endothelial cells participate to create an immunosuppressive milieu that results engulfed of tolerogenic factors and interleukins (IL) as IL-6 and IL-10. To underline the role of the immune infiltrate in blocking the melanoma progression, it has been described that the composition, density, and distribution of cytotoxic T-cells in the surrounding stroma is predictive of responsiveness to immunotherapy. Here, we review the major mechanisms implicated in melanoma progression, focusing on the role of DCs.